No-till only increases N₂O emissions in poorly-aerated soils - Rochette, Philippe (Soil & tillage research, 2008)
Denitrification rates are often greater in no-till than in tilled soils and net soil-surface greenhouse gas emissions could be increased by enhanced soil N₂O emissions following adoption of no-till. The objective of this study was to summarize published experimental results to assess whether the response of soil N₂O fluxes to the adoption of no-till is influenced by soil aeration. A total of 25 field studies presenting direct comparisons between conventional tillage and no-till (approximately 45 site-years of data) were reviewed and grouped according to soil aeration status estimated using drainage class and precipitation during the growing season. The summary showed that no-till generally increased N₂O emissions in poorly-aerated soils but was neutral in soils with good and medium aeration. On average, soil N₂O emissions under no-till were 0.06kgNha⁻¹ lower, 0.12kgNha⁻¹ higher and 2.00kgNha⁻¹ higher than under tilled soils with good, medium and poor aeration, respectively. Our results therefore suggest that the impact of no-till on N₂O emissions is small in well-aerated soils but most often positive in soils where aeration is reduced by conditions or properties restricting drainage. Considering typical soil C gains following adoption of no-till, we conclude that increased N₂O losses may result in a negative greenhouse gas balance for many poorly-drained fine-textured agricultural soils under no-till located in regions with a humid climate.